The value, challenges and practical considerations of conducting qualitative research on antimicrobial stewardship in primary care - Wanat, M; Santillo, M; Borek, A; Butler, C; Anthierens, S; Tonkin-Crine, S (Oxford University Press, 2022)
In order to design appropriate antimicrobial stewardship (AMS) programmes, it is crucial to understand challenges to tackling antibiotic resistance (AMR) specific to each healthcare setting. Antibiotic prescribing in primary care accounts for most prescriptions with a significant proportion considered clinically inappropriate. Qualitative research has a long history in social sciences, but its value and contribution are still contested in medical journals including in the AMR/AMS field. However, through its focus on understanding, meaning making and explaining, qualitative research can offer insights in how to improve AMS efforts in primary care. This paper provides an overview of unique considerations, contributions and challenges related to using qualitative research in AMS to help the AMS community new to qualitative research to utilize its potential most fully. First, we discuss specific considerations for AMS in relation to the stages of conducting a qualitative study, including identifying a research question and choosing a suitable methodology; sampling appropriate participants; planning a recruitment strategy; choosing a method of data collection; and conducting data analysis. These are illustrated with examples of qualitative AMS studies in primary care. Second, we highlight the importance of patient and public involvement throughout all stages of the project and ensuring quality in qualitative AMS research. Finally, drawing on these considerations, we make a further case for the value and contribution of qualitative methodologies in AMS/AMR research while outlining future directions for both AMS and qualitative research, including the need for studies with diverse actors; interdisciplinary collaborations; and complex decisions on methodologies and timelines.